The Integration of Social Issues in Design Education as a Catalyst towards Social Sustainability - Kazamia, Kika Ioannou; Kafaridou, Marianna (European Journal of Sustainable Development, 2019)
This research focuses on how to enforce the social pillar of sustainability through design education and more specifically through an assignment of a real-life project given to design students. This need derived from previous research, which suggests that „change? towards social sustainability, should focus on two sectors: Education and industry. In this study, the suggestion will be realized through a proposed real-life project that aims at the promotion of literacy in a children?s hospital environment. All students are involved in a creative design process starting with the problem analysis, which requires the identification of the nature and requirements of the task and the development of a plan of ideas and mechanisms, to answer the brief. Then they proceed with visual and textual research and conceptual development. Students generate concepts, produce rough ideas and explore a number of visual answers to the brief, which are analyzed in terms of project objectives. Project development is the next stage where ideas are further developed and explored implementing appropriate methods and techniques. The final stage of the process includes the final presentation, critique, feedback and then its realization. Through the above design process, the students acknowledged the needs of the community and how social issues can be assimilated in a design project to satisfy and enhance the social pillar of sustainability. Keywords: Design; Education; Social Sustainability